Broad-scale spatial distribution patterns of soft-sediment macrobenthic communities in the Red Sea - Susana Carvalho; Zahra Alsaffar; Joanne Ellis; Hamed Alghamdi; João Cúrdia (Frontiers in Marine Science, 2023)
In sub-tropical and tropical regions, the diversity patterns of soft-sediment macrobenthic communities are still poorly understood, particularly when compared to temperate shelf environments. The present study investigates spatial patterns of variability in macrobenthic distribution along the eastern Red Sea margin, and the role of sediment composition and other explanatory variables in determining such patterns. This study has two main objectives: (i) to produce a baseline characterization of the Saudi Arabian Red Sea macrobenthic infauna, particularly along the central and southern regions, (ii) to assess the relative contribution of two major processes driving macrobenthic communities (i.e., dispersal-based and environmental filtering), based on changes on beta-diversity components (turnover and nestedness) across multiple scales (up to ~600km), using relevant modeling methodologies. Shallow soft-sediment macrobenthic communities in the Red Sea showed extremely high small-scale variability, highlighted by the percentage of rare species (44% of species present at a single sample) and the dominance of turnover (species replacement) over nestedness. Our results also suggest a strong influence of broad- over fine-scale variation in the species composition. However, sedimentary characteristics, particularly grain-size, played a critical role governing the distribution patterns of soft-sediment macrobenthic communities in the Red Sea. Our findings highlight the importance of regional factors in shaping the macrofaunal community composition whilst also highlighting the role of high species diversity at local scales. The current results suggest the need for conservation measures from regional levels (to maintain genetic diversity) to local levels (to preserve the high occurrence of rare species). To our knowledge, no other study investigated the distribution of Red Sea marine species over large spatial scales combining modeling methods and the partitioning of beta-diversity. The current approach applied to soft-sediment macroinvertebrates can be extended to other marine communities since conservation strategies can be more effective when mechanisms governing species distribution are considered.